2019
DOI: 10.1097/nt.0000000000000385
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Content and Ingredients of Commercial Infant and Toddler Food Pouches Compared With Other Packages Available in the United States

Abstract: The ingredients and nutrients of infant and toddler foods (ITFs) sold in pouches were compared with products available in other packages, such as jars/packs and other containers. Company websites (n = 21) and in-store shelf inventory (n = 3) were used to create a database of commercial ITFs containing vegetables (n = 548) sold in the United States. Results indicated that ITFs containing vegetables were most commonly packaged in pouches (50%), followed by “other” packages (25%) and jars/packs (25%). Infant and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 17 publications
3
20
0
Order By: Relevance
“…Koletzko et al [ 18 ] reported that pouches available in Germany contained predominantly sweet, puréed fruit preparations, which were typically the source of the majority (or even all) of their sugars content. Moding et al [ 8 ] reported that the high sugars content of pouches available in the USA is driven by the presence of fruits and vegetables that are naturally higher in sugars, as has been reported for commercial infant foods in general in the UK [ 37 ]. Moreover, a recent study of commercially available complementary foods in New Zealand reported that “relatively sweet” vegetables were used more frequently than “bitter” vegetables [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Koletzko et al [ 18 ] reported that pouches available in Germany contained predominantly sweet, puréed fruit preparations, which were typically the source of the majority (or even all) of their sugars content. Moding et al [ 8 ] reported that the high sugars content of pouches available in the USA is driven by the presence of fruits and vegetables that are naturally higher in sugars, as has been reported for commercial infant foods in general in the UK [ 37 ]. Moreover, a recent study of commercially available complementary foods in New Zealand reported that “relatively sweet” vegetables were used more frequently than “bitter” vegetables [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to report the “free sugars” and “added sugars” content of commercial infant foods. The finding that pouches, on average, did not contain any free or added sugars was surprising, particularly given the widespread concern about high sugars content in pouches, and the emphasis being placed on the sugars content of commercial infant foods in the literature [ 8 , 28 , 43 ]. The WHO Regional Office for Europe made a call in 2019 to ban added sugars and “sweetening agents” (including fruit juices and fruit juice concentrates) in commercially available complementary foods [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Furthermore, epithelial injury and dysfunction [3][4][5] has recently become a focus of allergic disease of the skin, airways, and esophagus. [11][12][13][14] The incidence of food allergy is increasing 6 in both the western and eastern world, and new allergic enteropathic conditions such as eosinophilic esophagitis and GORD. 7,8 Diet histories taken at an allergy clinic showed an observed increasing trend in the use of commercial infant/toddler foods by parents of infant and toddlers diagnosed with eosinophilic esophagitis (EoE) and gastro-esophageal reflux disease (GORD).…”
Section: Is the Low Ph Of Infant And Toddler Foods A Concern?mentioning
confidence: 99%